Dinâmica de floresta ombrófila densa submetida ao manejo madeireiro e incêndio na Amazônia oriental - Costa, Daniele Lima da (2020)
Many areas of the Amazon rainforest are currently under timber management, with a cutting cycle of 25 to 35 years. The estimates of the forest recovery generated for the next cutting cycle is the subject of many studies and opinions about its sustainability. In addition to the doubt about the recovery of these areas for the next cutting cycle, forest fires that occur frequently in the Amazon Forest, affect managed areas and can render the activity unfeasible within the current management cycle. There is little knowledge about the recovery of managed forests, and within this problem or the best path is the development of new studies that are available and monitor their recovery. Thus, the objective of this study was to evaluate a floristic, structural composition and an Ombrophilous Dense forest under wood management and affected by accidental fire in the Eastern Amazon. Areas of managed forest (FM) and unmanaged forest (WSF) in the Tapajós National Forest, state of Pará, were evaluated in an annual production unit (UPA), managed in 2010. A total of 93 and 58 permanent plots, respectively, were used to monitor FM and WSF. The first measurement was carried out in 2010, before logging, with successive remeasurement in 2011, 2015, 2016 and 2017. In 2015 after the remeasurement, there was an accidental fire that reached all 151 permanent plots and, therefore, the remeasurement of 2016 and 2017 from FM and FSM were executed under the disturbance caused by the fire. The capacity of floristic and phytosociological structure was evaluated; species diversity and similarity; mortality and ingrowth rates; diametric classes of dead trees: diametric increment; and use only commercial species, in the previous periods (2010-2015) and (2016-2017) post fire, with the use of identifying the main effects of management and fire under FM and FSM areas. Management and fire have caused significant changes in number of trees and basal area over the years. There was greater ingrowth and mortality in the forest managed in the period before the fire. After the fire, the reductions in the number of trees and the basal area were proportionally similar to the FM and FSM, in both, the reduction in trees was greater than 40% in relation to the last measurement before the fire. Larger representative families and species had higher mortality and ingrowth, with no change in the importance value of species over the years. There was an increase in species diversity five years after management and a reduction in species similarity in two years after the FM fire. As mortality and ingrowth rates of all species and only commercial animals were higher in FM both before and after the fire. The diametric growth of the trees was greater after the fire. Commercial species that demand light that have a low density before the fire, showed higher ingrowth after the disturbance caused by the fire. The disturbances caused by the management and the fire contributed to alterations in the structure and floristics of the FM and FSM immediately after its occurrence. The smallest species similarity after the fire did not suffer loss of species diversity, but possibly the largest ingrowth of pioneers after the fire. The fire caused an imbalance in mortality and ingrowth ratesafter its occurrence, both for the community and only for commercial species. It is necessary to continue monitoring the recovery of the FM and the FSM under the disturbance caused by fire for a longer period in order to more definitively assess the effect of this natural occurrence.